To Study the Consumer Attitude Towards Purchase Intention of Online Courses on Udemy Using Regression with Reference to English Speaking and Excel Among Gen-Z in Ahmedabad - Chandni J. Vidani; Shashwat Sharma (MultiTech Publisher, 2023)
This research paper investigates the consumer attitudes toward the purchase intention of online courses on Udemy, with a specific focus on English speaking and Excel courses among Generation Z individuals in Ahmedabad, India. Using a mixed-methods approach, data was collected through a survey questionnaire administered to a sample of Generation Z participants in Ahmedabad. The questionnaire captured demographic information, assessed consumer attitudes towards online courses, and measured the purchase intention specifically related to English speaking and Excel courses on Udemy. The acquired data was evaluated using a regression approach to determine the elements impacting purchase intentions and to comprehend the magnitude and trend of the correlations. This study's findings provide useful insights into customer views toward online courses, emphasizing the elements that influence purchasing intentions. The study's results have implications for marketing strategies and course development for online education platforms like Udemy. Understanding consumer attitudes and preferences can inform the creation of targeted promotional campaigns, course offerings, and pricing strategies tailored to the specific needs and preferences of the Generation Z population in Ahmedabad. This research contributes to the existing literature on consumer behavior and online education, providing practical implications for educational platforms and educators